(untitled) (Iter, 2022)
Ximena Godoy Arcaya ’s Fromwolves and from the eagle, presents lyrics themes or motifs from the italian poetry. The trip subject, the characters of Saint Francisco and Saint Cecilia, the presence of the Donna and the Erosy the image of the wolf and the descent to the underworld are among them. The tone, lyric imagesy the semantic concentration and liguistic softeness abridge from the text a highly aesthetic poetic nucleus.